43. The Capsule and Beyond: Genetic Determinants of Pediatric streptococcus Pneumoniae empyema. (31st December 2020) - Pershing, Nicole L; Kapusta, Aurelie; Nielsen, Shannon; Crandall, Hillary; Korgenski, Kent; Byington, Carrie L; Ampofo, Krow; Blascke, Anne
Abstract: Background: Streptococcus pneumoniae is the most common cause of pneumonia in children, including empyema, a severe complication with increasing incidence in the post-pneumococcal vaccine era. Only a subset of > 90 serotypes cause empyema. Virulence determinants of empyema remain largely unknown. Methods: We performed Illumina sequencing of invasive Pneumococcal isolates from pediatric patients at Primary Children's Hospital (Salt Lake City, UT) isolated between 1996–2018, de novo genome assembly (SPADES), annotation (PROKKA), serotyping (Quelling and SeroBA), and pan-genome assembly (ROARY). SCOARY and pyseer were used for microbial GWAS. Maximum likelihood phylogeny was calculated using RAxML/Gubbins. Results: 366 pneumococcal isolates were analyzed from 39 serotypes and multiple phenotypes including pneumonia (n=76), empyema (n=63), CNS infection (n=54), and isolated bacteremia (n=79). Serotypes and empyema phenotype clustered roughly by phylogeny. Most analyzed empyema isolates after 2010 were serotype 3 (19/25); prior to PCV-13 introduction serotypes 1 (8/38), 7F (7/38), and 19A (11/38) were more highly represented. Genes implicated in capsule synthesis, transposases, and metabolism were statistically correlated with the empyema phenotype. Conclusion: Specific capsular or metabolic genes may confer optimal fitness for pleural disease. Further characterization of these genetic associations is needed and will inform future treatment and prevention. Disclosures: Carrie L. Byington, MD, BioFire (Other Financial or Material Support, Royalties for Intellectual Property)IDbyDNA (Advisor or Review Panel member) Krow Ampofo, MBChB, Merck (Grant/Research Support)